Authentication of incense (Pittosporum undulatum Vent.) honey from the Azores (Mel dos Acores) by a novel real-time PCR approach - Lopes, Ana (2018)
'Mel dos Acores' is a unique nectar honey produced from the exceptional and diverse flora of the Azores archipelago, categorised as incense honey ('mel de incenso') or multifloral honey ('mel multiflora'). Incense honey should contain over 30 % of pollen grains of Pittosporum undulatum Vent. In this work, a real-time PCR method targeting the ITS region was proposed for the first time to detect P. undulatum in the honey from the Azores. The approach exhibited high analytical performance, achieving a quantification limit of 0.01 pg of incense DNA. The method was successfully applied to 22 honey samples, from which incense was detected in all 9 monofloral incense honeys and in 5 out of 10 multifloral samples from the Azores. Generally, the quantitative results for incense DNA were in good agreement with the melissopalynological data. Therefore, a simple, cost-effective and reliable tool was herein proposed to authenticate and valorise the Azores honey.